2022
DOI: 10.32598/jhnm.32.4.2216
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Anger, Moral Distress, and Self-esteem in Nurses

Abstract: Introduction: Due to stressful work conditions, nurses are constantly exposed to various emotions and stressors such as anger and moral distress that threaten their mental health. On the other hand, self-esteem is one of the personality traits essential for people's mental health and improving their performance. Objective: The present study investigates the relationship between anger, moral distress, and self-esteem in nurses. Materials and Methods: This analytical correlational study was conducted on nurses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This might be due to individuals lacking con dence may perform poorly for the challenge and exhibit negative reactions when confronted with failures, negative events, and psychosocial risk factors such as high workload, lack of support, patients' deaths and their families' grief, working in highly stressful wards, and patients suffering from chronic diseases and cancers. As a result, moral distress increases (33).…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to individuals lacking con dence may perform poorly for the challenge and exhibit negative reactions when confronted with failures, negative events, and psychosocial risk factors such as high workload, lack of support, patients' deaths and their families' grief, working in highly stressful wards, and patients suffering from chronic diseases and cancers. As a result, moral distress increases (33).…”
Section: Discussionmentioning
confidence: 99%
“…9 In the caring field, burnout means loss of feeling and interest in the patients and providing improper and non-standard care for them. 10 The COVID-19 pandemic has raised many challenges for HCWs 1 and affected the performance and job satisfaction of the front-line HCWs. 11 In a study on prehospital emergency medical personnel, Heidari et al found that personnel who directly cared for the patients with COVID-19 had higher symptoms of burnout.…”
Section: Introductionmentioning
confidence: 99%